Trends in Digital Personalized Learning: Landscape Review of Personalized Learning Solutions in Low and Middle-Income Countries - Castillo, Nathan M.; Adam, Taskeen; Alam, Andaleeb; Alrawashdeh, Ghaida S; Tiwari, Priyamvada (UNICEF Office of Global Insight & Policy, 2022)
Digital Personalized Learning (DPL) - tech solutions and products that tailor learning to individuals and their specific learning needs - have the potential to improve learning outcomes and close gaps for students who have fallen behind. However, there is a limited of evidence from digital personalized learning interventions deployed across the developing world. This landscape review identifies trends and gaps in DPL implementation in low- and middle-income country (LMIC) contexts. This research report presents data on DPL effectiveness in LMICs from over 40 interventions worldwide by to classifying and categorizing design features, implementation models, and scalability factors. Implications for future research and design are discussed from a multi-stakeholder perspective.
Keywords: Global studies; Learning; Policy action; Quality of education; technology in education